PENGARUH PRODUCT QUALITY TERHADAP CUSTOMER PREFERENCE PADA PRODUK SAMSUNG DI SURABAYA DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING - Ronald Ronald (Jurnal Strategi Pemasaran, 2017)
This study was conducted to determine whether the Product Quality and Brand Image effect on Customer Preference on Samsung products in Indonesia, especially in the city of Surabaya in the middle of the competition Brand Smartphones are increasingly numerous and competing to provide advanced features as well as the development of technology which is fast enough so the researchers wanted to find out how the influence of Product Quality and Brand Image on Customer Preference. This research uses descriptive quantitative approach by distributing questionnaires to 100 respondents. Determination of respondents using purposive sampling technique which is based on consumers who never make purchases more than once in one of the smartphone Samsung in the city of Surabaya. The data obtained will be processed by the method of analysis of PLS (Partial Least Squares) in order to determine the influence between variables of the study.